2004
DOI: 10.1080/15476910490496258
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Involvement of Macrophages and T Cells in D-Penicillamine-Induced Autoimmunity in the Brown Norway Rat

Abstract: The initiating events in drug-induced autoimmunity are poorly understood and difficult to study. We examined the role of macrophages and T-cells in the Brown Norway rat model of D-penicillamine-induced autoimmunity. When activated, macrophages can act as both antigen presenting cells, initiating immune responses, and as phagocytic cells mediating systemic tissue damage. We found that B7(+) macrophages are the major antigen-presenting cell type infiltrating the spleen and caecum early in the response to Dpenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The fact that penicillamine caused rapid macrophage activation while the onset of autoimmunity occurs after about 3 weeks of treatment strongly suggests that macrophages play a role in the initiation of the immune response leading to autoimmunity. This is consistent with our previous study in which significant infiltration of activated macrophages into the cecum was found only 96 h after penicillamine treatment (27).…”
Section: Discussionsupporting
confidence: 94%
“…The fact that penicillamine caused rapid macrophage activation while the onset of autoimmunity occurs after about 3 weeks of treatment strongly suggests that macrophages play a role in the initiation of the immune response leading to autoimmunity. This is consistent with our previous study in which significant infiltration of activated macrophages into the cecum was found only 96 h after penicillamine treatment (27).…”
Section: Discussionsupporting
confidence: 94%
“…For instance, treatment of murine RAW264.7 macrophage cells with D -penicillamine activates these cells via direct binding of D -penicillamine to cell-surface aldehydes, resulting in increased production of cytokines TNF-α, IL-6, and IL-23 ( Li and Uetrecht, 2009 ). Likewise, D -penicillamine was shown to activate macrophages and T-cells, undergirding the ability of this compound to induce autoimmunity in Brown Norway rats ( Masson et al., 2004 ). Overall, D -penicillamine inhibits CSE and activates immune cells, in addition to other functions.…”
Section: H 2 S Research Tools: Inhibitors Of H mentioning
confidence: 99%
“…The T cell inhibitor tacrolimus can prevent disease onset, reverse ongoing disease, and prevent disease relapse upon re-exposure to D-penicillamine in this mouse model, emphasizing the importance of a T cell role in the mechanism of disease. Experimental depletion of macrophages significantly decreases the incidence of the disease, so both cell types and probably their interaction are important in inducing drug-related autoimmune disease [30]. Enhanced macrophage activation, and increased expression of allele 3 of the solute carrier family 11 member a1 (SLC11A1), has been shown to be associated with autoimmune disease [31].…”
Section: The Effects Of Inhibition Of Dna Methylation On Peripheral Tmentioning
confidence: 99%